Improving the dietary quality of food parcels leads to improved dietary intake in Dutch food bank recipients—effects of a randomized controlled trial - Neter, Judith E. (Eur J Nutr, 2020)
PURPOSE: Since food banks have a strong influence on recipients’ diets, and seem to have difficulties in supporting healthy diets, improving the dietary quality of food parcels is important. The aim of our study was to assess whether improving the dietary quality of food parcels, using different strategies, can positively impact the actual dietary intake of Dutch food bank recipients. METHODS: This randomized cross-over controlled trial (Trial ID: ISRCTN40554133) with four intervention conditions [(1) Control (standard food parcel), (2) snacks(–) (standard food parcel with replacement of unhealthy snacks by staple foods), (3) FV(+) (standard food parcel plus the recommended daily amount of fruit and vegetables), (4) snacks(–) + FV(+) (standard food parcel with replacement of unhealthy snacks by staple foods plus the recommended daily amount of fruit and vegetables)] included 163 food bank recipients, from three food banks. At baseline, participants filled in a questionnaire. Dietary intake data were collected through 24-h recalls after both intervention conditions at 4 and 8 weeks follow-up. Primary outcome was daily fruit and vegetable intake, secondary outcomes were daily dietary intakes of food groups and nutrients. RESULTS: Multi-level linear regression analysis, using a two-level model, showed a higher mean daily fruit intake in participants in the FV(+) condition than in participants in the Control condition (delta (δ): 74 [40.3;107.6] g). Both mean daily fruit and vegetable intake were higher in participants in the Snacks(–) + FV(+) condition than in participants in the Control condition (fruit δ: 81.3 [56.5;106.2] g; vegetables δ: 46.2 [17.5;74.9] g), as well as in the Snacks(–) condition (fruit δ: 70.0 [38.8;101.1] g; vegetables δ: 62.2 [26.2; 98.2] g). CONCLUSIONS: This study shows that improving the dietary quality of food parcels can positively impact the dietary intake of Dutch food bank recipients. With this information we can further develop effective strategies that can be easily applied by food banks, to improve dietary intake of food bank recipients.